Tolerance Limit for Trucks with Excess Load in Transport Regulation in Indonesia - Hadiwardoyo, Sigit Pranowo; Sumabrata, Raden Jachrizal; Berawi, Mohammed Ali (UI Scholars Hub, 2012)
Reliability of a road is mandatory since damaged will impede the traffic. Destruction is caused by various factors; one of the most important factors is excess load. Overload may give the load of each axle of a vehicle exceeds the determined standard. This condition occurs in trucks exceeding the load limit. In designing the structure of a road based on the method of Directorate General of Highways Ministry of Public Works of the Republic of Indonesia, axle load calculated in equivalent-number, or known as equivalent axle load (EAL), of 8.16 tons of standard axle. Total equivalent-number over the service life is defined as cumulative equivalent standard axle load (CESA). Due to traffic volume exceeding the volume forecast or, in other words there is an excessive load of traffic, it will make CESA achieved faster than planned. This excessive load in Indonesia, however, has been considered as a factor of environmental condition, so there is a need to introduce a correction factor for EAL as high as 20-25% in the process of designing flexible and rigid pavement so as to reduce early damage.